2018
DOI: 10.1016/j.biopsycho.2017.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Emotional eating and instructed food-cue processing in adolescents: An ERP study

Abstract: We examined the P3 (250-500ms) and Late Positive Potential (LPP; 500-2000ms) event-related potentials (ERPs) to food vs. nonfood cues among adolescents reporting on emotional eating (EE) behavior. Eighty-six adolescents 10-17 years old were tested using an instructed food versus nonfood cue viewing task (imagine food taste) during high-density EEG recording. Self-report data showed that EE increased with age in girls, but not in boys. Both P3 and LPP amplitudes were greater for food vs. nonfood cues (food-cue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 66 publications
(105 reference statements)
4
20
0
4
Order By: Relevance
“…After the rest, a progressive muscle relaxation tape was played for 5 minutes, followed by instructed relaxation exercises for 10 minutes. Next, T2 measurements were taken (T2, + min 40), followed by an EEG food cue viewing task was administered (7 min) (Wu et al, 2017), and a computer-based reward task was administered the first time (8-min) (Crowley et al, 2013). Then either the TSST-C or IC procedure was conducted (15 min).…”
Section: Methodsmentioning
confidence: 99%
“…After the rest, a progressive muscle relaxation tape was played for 5 minutes, followed by instructed relaxation exercises for 10 minutes. Next, T2 measurements were taken (T2, + min 40), followed by an EEG food cue viewing task was administered (7 min) (Wu et al, 2017), and a computer-based reward task was administered the first time (8-min) (Crowley et al, 2013). Then either the TSST-C or IC procedure was conducted (15 min).…”
Section: Methodsmentioning
confidence: 99%
“…This study builds upon the literature by exploring mechanisms by which food cravings are linked to increased problematic eating behaviors during late adolescence, which is a developmental period with known risks of unhealthy eating, weight change, and behavioral regulation abilities [4,20]. Greater EA has been associated with eating disorder symptomology [33,34], but less research has examined EA and eating behaviors within non-clinical samples.…”
Section: The Present Studymentioning
confidence: 99%
“…Women who did not meet criteria for BED, but still reported binge eating episodes, experienced higher levels of negative affect, perceived loss of control, and higher levels of food cravings, compared to women without BED and no binge eating episodes [1]. More specific to adolescents (ages 10–17), researchers examining emotional eating adolescents’ neural responses suggested that food images produced stronger neural activations than non-food images [20]. These findings illustrate the rationale to examine mechanisms by which obsessive thoughts or cravings for food associate with for problematic eating late adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…However, when instructed to regulate food cravings, these areas showed decreased activation in heavier children [33]. Comparable to EEG findings in adults, both P300 and LPP amplitudes were found to be higher for highcalorie food cues, with higher LPP amplitudes in emotional eaters [34]. However, P300 amplitudes for mixed low-and high-calorie food cues were comparable for obese and normal-weight adolescents [35].…”
Section: Introductionmentioning
confidence: 99%